MNSFβ Regulates TNFα Production by Interacting with RC3H1 in Human Macrophages, and Dysfunction of MNSFβ in Decidual Macrophages Is Associated With Recurrent Pregnancy Loss - Zhen, Xing-Xing; Yang, Long; Gu, Yan; Yang, Qian; Gu, Wen-Wen; He, Ya-Ping; Wang, Yan-Ling; Wang, Jian (Frontiers in Immunology, 2021)
Decidual macrophages (dM) are the second largest population of leukocytes at the maternal-fetal interface and play critical roles in maintaining pregnancy. Our previous studies demonstrated the active involvement of monoclonal nonspecific suppressor factor- (MNSF) in embryonic implantation and pregnancy success. MNSF is a ubiquitously expressed ubiquitin-like protein that also exhibits immune regulatory potential, but its function in human dM remains unknown. Here, we observed that the proportion of CD11chigh (CD11cHI) dM was significantly increased in dM derived from patients with recurrent pregnancy loss (RPL dM) compared to those derived from normal pregnant women (Control dM). The production of MNSF and TNF by RPL dM was also significantly increased compared to that by Control dM. Conditioned medium from RPL dM exerted an inhibitory effect on the invasiveness of human trophoblastic HTR8/SVneo cells, and this effect could be partially reversed by a neutralizing antibody against TNF. Bioinformatics analysis indicated a potential interaction between MNSF and RC3H1, a suppressor of TNF transcription. Immunoprecipitation experiments with human M differentiated from the human monocyte cell line Thp1 (Thp1-derived M) proved the binding of MNSF to RC3H1. Specific knockdown of MNSF in Thp1-derived M led to a marked decrease in TNF production, which could be reversed by inhibiting RC3H1 expression. Interestingly, a significant decrease in the protein level of RC3H1 was observed in RPL dM. Together, our findings indicate that aberrantly increased MNSF expression in dM may promote TNF production via its interaction with RC3H1, and these phenomena could result in the disruption of the immune balance at the maternal-fetal interface and thus pregnancy loss.